Examining the Moderating Role of Educational Intervention in the Relationship between Family Background and Career Adaptability (Journal of Educational Sciences, 2026)
This study aims to explore the moderating role of school career education in the relationship between family socioeconomic status (SES) and the career adaptability of university students. Grounded in social capital theory and career construction theory, we hypothesize that while family background significantly influences students’ career adaptability, systematic school-based career education can mitigate this effect, thereby fostering a more equitable competitive environment. Methodology and Methods: using a cluster sampling method, 650 undergraduate students from Huanggang City and Huangshi City in Hubei Province, China, were surveyed. After excluding invalid responses, 618 valid questionnaires were retained (95.0% effective response rate). Hierarchical regression analysis was employed to test the main and moderating effects. Results: the findings indicate that: (1) Family SES significantly and positively predicts students’ career self-concept clarity, career adaptability, and career exploration behaviors; (2) The participation level and quality of school career education independently and positively influence students’ career adaptability; (3) Most importantly, career education plays a significant negative moderating role in the relationship between family background and career adaptability. Specifically, career education has a stronger enhancing effect on the career adaptability of students from disadvantaged family backgrounds. Scientific novelty. This study empirically validates the “compensatory effect” of school career education, demonstrating its role as a “social leveler” that can disrupt the intergenerational transmission of educational inequality. Practical significance: the results suggest that systematic, highquality school career education is an effective intervention strategy for promoting educational equity, compensating for deficiencies in family capital, and preparing all students, particularly those from disadvantaged backgrounds, for their future careers.Keywords: career education, family background, career adaptability, educational equity, moderating effect.